Long-term results of medical treatment for lower extremity stress fractures - M. S. Ryazantsev; A. R. Zaripov; A. P. Afanasyev; M. N. Maysigov; N. E. Magnitskaya; D. O. Ilyin; A. N. Logvinov; A. V. Frolov; A. V. Korolev (Научно-практическая ревматология, 2020)
Objective: to assess the long-term results of medical treatment for lower extremity stress fractures.Subjects and methods. Fifty-five patients who had received a medical treatment cycle in the European Clinic of Sports Traumatology and Orthopedics (ECSTO) in the period 2010 to 2016 were followed up. The patients' mean age was 37 (range 15—65) years. Among them, there were 36 (65%) females and 19 (35%) males. The long-term results of treatment were assessed using the Foot and Ankle Ability Measure (FAAM) scale (ADL + sport modules) and the Lower Extremity Functional Scale (LEFS) scales.Results and discussion. Assessing the degree of stress adjustment according to magnetic resonance imaging (MRI), on visiting, in accordance with the classification proposed by E.A. Arendt et al., revealed grades 2, 3, and 4 injuries in 10 (18%), 14 (26%), and 16 (29%) patients, respectively. The median time from the moment of visiting before assessment according to the orthopedic scales was 3 years (1 to 7 years). The second and third metatarsals underwent stress adjustment in 25 (47%) patients. The cause of stress adjustment was most often running (38%), less often walking (29%), playing sports (18%), fitness (9%), and other types of physical activity (6%). Assessing the scores for the FAAM ADL and FAAM sport subscales showed that the median was 100 [96; 100]% and 100 [91; 100]%, respectively. Estimating the scores for the LEFS scale revealed excellent, good, and satisfactory results in 48 (87%), 6 (11%), and in 1 (2%) patients, respectively.Conclusion. The most common cause of lower extremity stress fractures is running. These changes respond well to medical treatment, which includes injured limb overuse, physiotherapy, and individual ankle-foot orthosis.